ESTIMATION AND MODELLING OF VOLATILITY IN THE MALAYSIAN STOCK MARKET - Mohd Jefrie, Mohd Adza; Bujang, Imbarine; Tuyon, Jasman; anak Nipo, Debbra Toria (Malaysian Journal of Business and Economics (MJBE), 2020)
Last three decades, the issues on the volatility of the stock market have attracted many researchers, academics and also the players in the financial market. In the stock market investors and researchers able to use the stock market index to measure the volatility. Volatility considered as the measurement for the uncertainty of fluctuation of stock price and measurement of risk. This paper intends to shed light the volatility behaviour via the persistency and leverage effect in the Malaysian stock market. The data of this paper starting from 2000 until 2018 and employ symmetric and asymmetric volatility model with a different distribution. The symmetric model can capture via Generalized Autoregressive Conditional Heteroscedasticity (GARCH) while asymmetric shock using Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) and Threshold Generalized Autoregressive Conditional Heteroscedasticity (TGARCH). The GARCH model showed weekly data of FTSE BM KLCI, FTSE BM Top100, FTSE BM Mid70 and FTSE BM Small presence of volatility clustering and persistence effect on the stock market volatility. Besides, asymmetric models found that weekly data, only several indices found the leverage effect. The best fit model also provided in the results and discussion.